English and Vietnamese idioms: from traditional to cognitive view - Nguyen , Ngoc Vu (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Classification and identification of idioms have always been an issue for linguists in nearly all languages. Referring to both Vietnamese and English literature of idioms, this article analyzes the current problems arising in traditional view and then discuss the alternative view from cognitive linguistics. From the analysis of some English and Vietnamese idioms, this article suggests that image schemas play an important role in forming idioms’ meaning.